Analysis on Al6061-NI-graphite composite using squeeze casting method - Arunkumar, S; Chandrasekaran, M; Vinod Kumar, T; ., . (International Journal of Engineering and Technology, 2018)
In recent years, aluminum based composites have gained popularity in all the popularity in all emerging fields of technology owing to their superior stiffness and strength. This is because of the less wetting nature between the fortification and the framework and the difficulty of higher level of support expansion in to the grid. Notwithstanding, metal covered fortifications have possessed the capacity to beat these confinements to an exceptionally degree. NCG particles strengthened Al6061 network with different weight rates were manufactured by crush throwing strategy. The main advantages of composite materials are their high strength and stiffness, combined with low density, when compared with bulk materials, sanctioning for a weight reduction in the culminated part.Aluminium based composite materials are leading ones in this area; they are fabricated using many methods, including squeeze casting pro-cesses. Squeeze casting makes materials properties relatively easy to control by mixing materials with different properties in various propor-tion. Samples of [5] and 10-wtpercentage reinforcement additament were synthesized and characterized. Heat transfer coefficients during squeeze cast of commercial aluminium were determined, by using the solidification temperature versus time curves obtain for varying applied pressure during squeeze casting process.Â